Breathomics—exhaled volatile organic compound analysis to detect hepatic encephalopathy: a pilot study. (11th February 2016) - Arasaradnam, R P; McFarlane, M; Ling, K; Wurie, S; O'Connell, N; Nwokolo, C U; Bardhan, K D; Skinner, J; Savage, R S; Covington, J A
Abstract: The current diagnostic challenge with diagnosing hepatic encephalopathy (HE) is identifying those with minimal HE as opposed to the more clinically apparent covert/overt HE. Rifaximin, is an effective therapy but earlier identification and treatment of HE could prevent liver disease progression and hospitalization. Our pilot study aimed to analyse breath samples of patients with different HE grades, and controls, using a portable electronic (e) nose. 42 patients were enrolled; 22 with HE and 20 controls. Bedside breath samples were captured and analysed using an uvFAIMS machine (portable e-nose). West Haven criteria applied and MELD scores calculated. We classify HE patients from controls with a sensitivity and specificity of 0.88 (0.73–0.95) and 0.68 (0.51–0.81) respectively, AUROC 0.84 (0.75–0.93). Minimal HE was distinguishable from covert/overt HE with sensitivity of 0.79 and specificity of 0.5, AUROC 0.71 (0.57–0.84). This pilot study has highlighted the potential of breathomics to identify VOCs signatures in HE patients for diagnostic purposes. Importantly this was performed utilizing a non-invasive, portable bedside device and holds potential for future early HE diagnosis.